Indole 3-acetic acid production and growth-promoting effect of Desertifilum sp. PSL17 on Vigna radiata - Palraj, Paheshwari; Subramani, Umasankar; Zimik, Zingran; Paranthaman, Sripriya (Frontiers in Industrial Microbiology, 2025)
Cyanobacteria are widely distributed across numerous ecosystems that include aquatic, terrestrial as well as extreme habitats such as the polar regions, hypersaline waters, hot springs, and deserts. They are known to play a key role in bringing oxygen on Earth. The present investigation reports the potential of Desertifilum sp. PSL17, a freshwater blue-green algae, to produce indole 3-acetic acid (IAA) and ammonia and also trigger the efficient germination of rice and promote the growth of green gram (Vigna radiata). Desertifilum sp. PSL17 was found to produce significant amounts of IAA (87.3 µg/mL) under optimal growth conditions. Tryptophan (trp) induction, promoting a 2.3-fold increase in IAA production, signifies trp-mediated IAA production in Desertifilum sp. PSL17. Rice seeds exhibited remarkable germination ability in the presence of the alga in comparison to untreated seeds. When co-cultivated with green gram (Vigna radiata), it exhibited a profound impact on plant growth promotion, resulting in increased root length, shoot length, and biomass production compared to the control. The substantial production of IAA and ammonia by Desertifilum sp. PSL17 plays a pivotal role in plant growth promotion. Our findings suggest that this freshwater Desertifilum sp. PSL17 has enormous prospective as a biofertilizer for promoting sustainable agriculture practices, particularly for green gram cultivation.